2019
DOI: 10.3389/fmicb.2019.00401
|View full text |Cite
|
Sign up to set email alerts
|

Non-muscle Myosin II: Role in Microbial Infection and Its Potential as a Therapeutic Target

Abstract: Currently, the major measures of preventing and controlling microbial infection are vaccinations and drugs. However, the appearance of drug resistance microbial mounts is main obstacle in current anti-microbial therapy. One of the most ubiquitous actin-binding proteins, non-muscle myosin II (NM II) plays a crucial role in a wide range of cellular physiological activities in mammals, including cell adhesion, migration, and division. Nowadays, growing evidence indicates that aberrant expression or activity of NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 87 publications
1
8
0
Order By: Relevance
“…Small RNAs including small interfering RNAs (siRNAs) and microRNAs (miRNAs) are widely used to explore gene functions due to their features of targeting mRNA degradation (Tan et al . 2019 ), and also to be useful tools for efficiently inhibiting virus replication and interfering protein synthesis (Du et al . 2009 ; Wong et al .…”
Section: Novel Small Rnasmentioning
confidence: 99%
“…Small RNAs including small interfering RNAs (siRNAs) and microRNAs (miRNAs) are widely used to explore gene functions due to their features of targeting mRNA degradation (Tan et al . 2019 ), and also to be useful tools for efficiently inhibiting virus replication and interfering protein synthesis (Du et al . 2009 ; Wong et al .…”
Section: Novel Small Rnasmentioning
confidence: 99%
“…NM2A was also linked to viral and bacterial infectious diseases: Its depletion often impairs the dissemination of pathogens [ 210 ]. Infection studies demonstrated that pathogens such as Kaposi’s sarcoma-associated herpesvirus and Listeria monocytogenes target NM2A, inducing its phosphorylation, which is detrimental for cellular invasion [ 75 , 211 ].…”
Section: Nm2a In Diseasementioning
confidence: 99%
“…Heparan sulfate (HS), glutamate/cystine exchange transporter (X-CT), and dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) receptors are known to use by KSHV whilst EBV uses neuropilin1 (NRP1) and non-muscle myosin heavy chain IIA (NMHC-IIA) for epithelial cell entry ( Fig. 2 ) [ 4 , 5 , [64] , [65] , [66] ].…”
Section: Introductionmentioning
confidence: 99%
“…NMHC-IIA: The 250 kDa NMHC-IIA is an actin-binding protein having the properties of actin cross-linking and contraction which is regulated by the light and heavy chains phosphorylation [ 100 ]. The NMHC-IIA played an important role in many viruses’ infection including the porcine reproductive and respiratory syndrome virus, thrombocytopenia syndrome virus and herpesviruses [ 65 ]. Although, it is mainly located in the cell cytoplasm [ 59 , 64 ].…”
Section: Introductionmentioning
confidence: 99%